2022
DOI: 10.1093/gji/ggac467
|View full text |Cite
|
Sign up to set email alerts
|

A discontinuous Galerkin method for sequences of earthquakes and aseismic slip on multiple faults using unstructured curvilinear grids

Abstract: Summary Physics-based simulations provide a path to overcome the lack of observational data hampering a holistic understanding of earthquake faulting and crustal deformation across the vastly varying space-time scales governing the seismic cycle. However, simulations of sequences of earthquakes and aseismic slip (SEAS) including the complex geometries and heterogeneities of the subsurface are challenging. We present a symmetric interior penalty discontinuous Galerkin (SIPG) method to perform SEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 155 publications
0
12
0
Order By: Relevance
“…For example, a recent dynamic rupture simulation of the 2008 Wenchuan earthquake (Tang et al., 2021) did not include the Xiaoyudong fault in their multi‐fault system because of numerical stability issues. This problem may be addressed using the discontinuous galerkin (DG) method that better handles fault geometry complexities in dynamic rupture simulations (e.g., Ulrich, Gabriel, et al., 2019; Ulrich, Vater, et al., 2019; Wollherr et al., 2019), and also possibly for quasi‐dynamic earthquake sequence models (e.g., Kozdon et al., 2019; Uphoff et al., 2022). Besides the fault geometrical complexities, previous numerical studies have also indicated that a larger ratio between the width of seismogenic zone and the critical nucleation size ( h *) along with the variation of ( b − a )/ a will introduce more complexities in earthquake cycles and rupture pattern (Barbot, 2019; Cattania, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent dynamic rupture simulation of the 2008 Wenchuan earthquake (Tang et al., 2021) did not include the Xiaoyudong fault in their multi‐fault system because of numerical stability issues. This problem may be addressed using the discontinuous galerkin (DG) method that better handles fault geometry complexities in dynamic rupture simulations (e.g., Ulrich, Gabriel, et al., 2019; Ulrich, Vater, et al., 2019; Wollherr et al., 2019), and also possibly for quasi‐dynamic earthquake sequence models (e.g., Kozdon et al., 2019; Uphoff et al., 2022). Besides the fault geometrical complexities, previous numerical studies have also indicated that a larger ratio between the width of seismogenic zone and the critical nucleation size ( h *) along with the variation of ( b − a )/ a will introduce more complexities in earthquake cycles and rupture pattern (Barbot, 2019; Cattania, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Besides its wide application in fluid dynamics (e.g., Rhebergen et al, 2013), the DG method has also been applied in the geophysical community for modeling seismic wave propagation (Chung et al, 2015;Y. Zhang et al, 2019) and fault aseismic slips (Uphoff et al, 2022). It has also been utilized to discretize the level set formulation for multiphase fluid dynamics modeling (e.g., Jibben & Herrmann, 2017;Mousavi, 2014;Mousavi et al, 2016;Owkes & Desjardins, 2013;J.…”
Section: Methodsmentioning
confidence: 99%
“…The DG discretization is originally formulated for the neutron transport problem (Reed & Hill, 1973) and has since been widely applied to the modeling of hyperbolic conservation laws (Cockburn & Shu, 1991; Shu, 2014). Besides its wide application in fluid dynamics (e.g., Rhebergen et al., 2013), the DG method has also been applied in the geophysical community for modeling seismic wave propagation (Chung et al., 2015; Y. Zhang et al., 2019) and fault aseismic slips (Uphoff et al., 2022). It has also been utilized to discretize the level set formulation for multiphase fluid dynamics modeling (e.g., Jibben & Herrmann, 2017; Mousavi, 2014; Mousavi et al., 2016; Owkes & Desjardins, 2013; J. Zhang & Yue, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Segmentation may well be the most important factor that modulate the large earthquakes. Two recent implications of SEAS models hinted the possibility of more insight into the emergence of power-law distribution in large-scale and non-planar fault systems (Uphoff et al, 2022;Ozawa et al, 2022), where we could test the contribution of various factors to the frequency magnitude distribution.…”
Section: Frequency-magnitude Distributionmentioning
confidence: 99%